Water-absorbent resin composition
By rationally configuring the ratio of antibacterial metal and porous deodorant in the water-absorbing resin composition, the problem of urease inactivation caused by the combination of antibacterial metal and L-cystine is solved, and a high-efficiency deodorizing effect on urine containing L-cystine is achieved.
Patent Information
- Application Number
- CN202480012604.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-22
- Filing Date
- 2024-01-31
- Publication Date
- 2025-09-12
AI Technical Summary
When existing water-absorbent resin compositions absorb urine containing a large amount of L-cystine, the antibacterial metal binds to the L-cystine, resulting in a weakened urease inactivation effect and an inability to effectively inhibit the production of ammonia.
In a water-absorbent resin composition, a deodorant containing an antimicrobial metal and a porous deodorant are used in combination, and the ratio and total content of the porous deodorant to the antimicrobial metal are controlled to be 0.8% or more in the water-absorbent resin composition, and the total content is 0.10% by mass or more, thereby synergistically exerting a deodorizing function.
Even when absorbing urine containing a large amount of L-cystine, the water-absorbent resin composition can effectively suppress the generation of ammonia and achieve an excellent deodorizing effect.
Smart Images

Figure CN120641214A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a water-absorbent resin composition, and more particularly to a water-absorbent resin composition constituting an absorbent body suitable for use in sanitary materials such as disposable diapers, sanitary napkins, and incontinence pads. Background Art
[0002] In recent years, water-absorbent resins have been widely used in sanitary materials such as diapers, sanitary napkins, and incontinence pads.
[0003] As such a water-absorbing resin, a cross-linked product of a partially neutralized salt polymer of acrylic acid has excellent water absorption performance. Furthermore, since acrylic acid, the raw material, is readily available industrially, it has many advantages, such as stable quality, low production cost, and resistance to spoilage and deterioration. Therefore, it is considered a preferred water-absorbing resin.
[0004] Meanwhile, absorbent articles such as disposable diapers, sanitary napkins, and incontinence pads primarily consist of an absorbent core positioned in the center to absorb and retain body fluids such as urine and menstrual blood; a liquid-permeable topsheet (top sheet) positioned on the side that contacts the body; and a liquid-impermeable backsheet (back sheet) positioned on the opposite side. The absorbent core is typically composed of hydrophilic fibers such as pulp and a water-absorbent resin.
[0005] When such an absorbent body is used in, for example, sanitary materials, unpleasant odors such as ammonia may be generated from the absorbent body having absorbed body fluids, particularly urine, blood, sweat, and the like.
[0006] Prior art literature Patent Literature Patent Document 1: Japanese Patent Application Laid-Open No. 2001-323155 Summary of the Invention Technical problem to be solved by the invention When urine is absorbed by the absorbent, the urease in the urine is broken down by the action of urease possessed by urease-producing bacteria, producing ammonia.
[0007] The present inventors have attempted to inactivate urease by using a deodorant containing an antimicrobial metal such as silver, thereby inhibiting the urease-induced urea decomposition reaction and suppressing ammonia production. However, their research has revealed that when large amounts of L-cystine (a sulfur-containing amino acid) are present in urine, as in the case of patients with cystinuria, the antimicrobial metal binds to the L-cystine, weakening the urease inactivation effect of the antimicrobial metal and preventing a sufficient deodorizing effect.
[0008] A main object of the present invention is to provide a water-absorbent resin composition having an excellent deodorizing effect on urine containing a large amount of L-cystine.
[0009] Technical solutions to technical problems The present inventors conducted intensive research to address the above-mentioned issues. As a result, they discovered that, in a water-absorbent resin composition containing water-absorbent polymer particles, by using a deodorant containing an antimicrobial metal and a porous deodorant in combination, and further ensuring that the ratio (X / Y) of the content X (parts by mass) of the porous deodorant to the content Y (parts by mass) of the antimicrobial metal-containing deodorant is at least a predetermined ratio, and further ensuring that the sum (x + y) of the content x (mass %) of the porous deodorant and the content y (mass %) of the antimicrobial metal-containing deodorant in the entire water-absorbent resin composition is at least a predetermined ratio, the water-absorbent resin composition can exhibit a high deodorizing function against ammonia and the like, even when absorbing urine containing a large amount of L-cystine.
[0010] That is, the present invention provides an invention having the following structure.
[0011] Item 1. A water-absorbent resin composition comprising a deodorant containing an antimicrobial metal, a porous deodorant, and water-absorbent polymer particles. The ratio (X / Y) of the content X (parts by mass) of the porous deodorant to the content Y (parts by mass) of the antimicrobial metal-containing deodorant is 0.8 or more. The sum (x+y) of the content x (mass %) of the porous deodorant and the content y (mass %) of the antimicrobial metal-containing deodorant in the entire water-absorbing resin composition is 0.10 mass % or more.
[0012] Item 2. The water-absorbent resin composition according to Item 1, wherein the sum (x+y) of the content x (mass %) and the content y (mass %) is 0.50 mass % or less.
[0013] Item 3. The water-absorbent resin composition according to Item 1 or 2, wherein the antimicrobial metal contained in the antimicrobial metal-containing deodorant comprises at least one selected from the group consisting of silver, copper, zinc, bismuth, cobalt, aluminum, and nickel.
[0014] Item 4. The water-absorbent resin composition according to any one of Items 1 to 3, wherein the antimicrobial metal-containing deodorant comprises at least one selected from the group consisting of silver powder, silver (I) chloride, silver (I) oxide, and a substance supporting at least one metal ion of silver ion and zinc ion.
[0015] Item 5. The water-absorbent resin composition according to any one of Items 1 to 4, wherein the porous deodorant comprises at least one selected from the group consisting of activated carbon, silicon dioxide, and silicates.
[0016] Item 6. The water-absorbent resin composition according to any one of Items 1 to 5, wherein the median particle size of the antimicrobial metal-containing deodorant is 0.1 μ m~100 μ m, the median particle size of the porous deodorant is 1 μ m~100 μ m.
[0017] Item 7. An absorbent article comprising a deodorant containing an antimicrobial metal, a porous deodorant, and water-absorbing polymer particles. The ratio (X / Y) of the content X (parts by mass) of the porous deodorant to the content Y (parts by mass) of the antimicrobial metal-containing deodorant is 0.8 or more. The sum (x + y) of the content x (mass %) of the porous deodorant and the content y (mass %) of the antimicrobial metal-containing deodorant, based on the total amount of the antimicrobial metal-containing deodorant, the porous deodorant, and the water-absorbing polymer particles, is 0.10 mass % or more.
[0018] Effects of the Invention According to the present invention, a water-absorbent resin composition having an excellent deodorizing effect on urine containing a large amount of L-cystine can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Schematic diagram of the device for measuring the water absorption of physiological saline under a load of 4.14 kPa. DETAILED DESCRIPTION
[0020] In this specification, the term "comprising" includes "consisting essentially of" and "consisting of." Furthermore, in this specification, "(meth)acrylic acid" refers to "acrylic acid or methacrylic acid," and "(meth)acrylate" refers to "acrylate or methacrylate." It should be noted that "water-soluble" means a solubility of 5% by mass or greater in water at 25°C.
[0021] In addition, in this specification, the numerical value connected by "-" means the numerical range including the numerical values before and after "-" as the lower limit and upper limit. When multiple lower limits and multiple upper limits are separately described, any lower limit and upper limit can be selected and connected by "-".
[0022] 1. Superabsorbent Resin Composition The water-absorbent resin composition of the present invention is characterized by comprising an antimicrobial metal-containing deodorant, a porous deodorant, and water-absorbent polymer particles. The ratio (X / Y) of the porous deodorant content (X, parts by mass) to the antimicrobial metal-containing deodorant content (Y, parts by mass) is 0.8 or greater, and the sum (x + y) of the porous deodorant content (x, mass%) and the antimicrobial metal-containing deodorant content (y, mass%) in the entire water-absorbent resin composition is 0.10% or greater. The water-absorbent resin composition of the present invention, having these characteristics, exhibits an excellent deodorizing effect on urine containing a large amount of L-cystine. The water-absorbent resin composition of the present invention is described in detail below.
[0023] As described above, the present inventors have attempted to inactivate urease by using a deodorant containing an antimicrobial metal such as silver, thereby inhibiting the decomposition reaction of urea by urease and suppressing the production of ammonia. However, the present inventors' research has revealed the following problem: L-cystine (a sulfur-containing amino acid) is present in large quantities in urine, as in the urine of patients with cystinuria. This makes it easy for the antimicrobial metal to bind to L-cystine, weakening the urease inactivation effect of the antimicrobial metal and preventing a sufficient deodorizing effect. Furthermore, the present inventors have conducted extensive research and have discovered that, in a water-absorbent resin composition containing water-absorbent polymer particles, in addition to using an antimicrobial metal-containing deodorant and a porous deodorant, the ratio (X / Y) of the porous deodorant content X (parts by mass) to the antimicrobial metal-containing deodorant content Y (parts by mass) is set to 0.8 or greater, and further, the sum (x + y) of the porous deodorant content x (mass %) and the antimicrobial metal-containing deodorant content y (mass %) in the entire water-absorbent resin composition is set to 0.10 mass % or greater. This allows the antimicrobial metal-containing deodorant and the porous deodorant to function synergistically, resulting in the water-absorbent resin composition exhibiting a high deodorizing function against ammonia even when absorbing urine containing a large amount of L-cystine. This is presumably because the porous deodorant adsorbs L-cystine in urine, thereby suppressing the inactivation of urease by the antimicrobial metal-containing deodorant. Furthermore, the inactivation of urease by the antimicrobial metal-containing deodorant is appropriately exerted, thereby enabling the water-absorbent resin composition to exhibit a high deodorizing function against ammonia.
[0024] In the water-absorbent resin composition of the present invention, at least a portion of the antimicrobial metal-containing deodorant (e.g., 20% to 100% by mass, 50% to 100% by mass, 80% to 100% by mass, 90% to 100% by mass, 95% to 100% by mass, or 100% by mass of the total antimicrobial metal-containing deodorant) can be disposed on the surface of the water-absorbent polymer particles. Alternatively, at least a portion of the antimicrobial metal-containing deodorant can penetrate into the interior of the water-absorbent polymer particles. Furthermore, in the water-absorbent resin composition of the present invention, at least a portion of the porous deodorant (e.g., 20% to 100% by mass, 50% to 100% by mass, 80% to 100% by mass, 90% to 100% by mass, 95% to 100% by mass, or 100% by mass of the total antimicrobial metal-containing deodorant) can be disposed on the surface of the water-absorbent polymer particles. In the water-absorbing resin composition of the present invention, at least a portion of the antimicrobial metal-containing deodorant and at least a portion of the porous deodorant may be disposed on the surface of the water-absorbing polymer particles.
[0025] (Deodorant containing antibacterial metals) A deodorant containing an antimicrobial metal is a deodorant containing an antimicrobial metal. The antimicrobial metal is preferably a metal that inactivates urease. Here, "antimicrobial metal" refers to at least one selected from the group consisting of gold, silver, copper, platinum, zinc, bismuth, titanium, tungsten, nickel, iron, tin, mercury, lead, palladium, aluminum, cobalt, molybdenum, chromium, vanadium, and zirconium. Furthermore, a "deodorant containing an antimicrobial metal" is a deodorant containing an antimicrobial metal to such an extent that it exerts a substantial antimicrobial effect, for example, a deodorant containing 1% or more of an antimicrobial metal (based on the total amount of two or more antimicrobial metals). The antimicrobial metal-containing deodorant is, for example, contained in a water-absorbent resin composition in a granular form.
[0026] Since the water-absorbent resin composition of the present invention is typically used in sanitary materials such as diapers and an excellent urease inactivation effect can be expected, the antimicrobial metal may contain at least one selected from silver, copper, zinc, bismuth, cobalt, aluminum, and nickel, may contain at least one selected from silver, copper, and zinc, or may contain at least one of silver and zinc.
[0027] Examples of deodorants containing antimicrobial metals include at least one selected from silver powder, silver (I) chloride, silver (I) oxide, and materials carrying at least one of silver and zinc ions. The material that supports the metal ions (support) may be, for example, a porous material. The porous material may include, for example, at least one selected from zeolite, activated carbon, silica, silicates, titanium dioxide, aluminum oxide, aluminum hydroxide, and magnesium hydroxide. It may also include at least one selected from zeolite, activated carbon, and silica, or it may include zeolite. Specifically, silver-zinc zeolite is preferred as the porous material carrying silver and zinc ions.
[0028] It should be noted that when the material serving as a carrier of metal ions is a porous material, the porous material may be a material capable of functioning as a deodorant by itself. In this case, the porous material and the porous deodorant described below may have the same chemical composition or different chemical compositions.
[0029] From the viewpoint of more appropriately exerting the effects of the present invention, when the antimicrobial metal-containing deodorant is contained in the water-absorbent resin composition in a granular form, the median particle size (D50 (median diameter), volume basis) of the antimicrobial metal-containing deodorant may be 0.1 μ m~100 μ m, 0.1 μ m~50 μ m, 0.1 μ m~10 μ m, 0.1 μ m~5 μ m, 0.1 μ m~3 μ m, 0.5 μ m~100 μ m, 0.5 μ m~50 μ m, 0.5 μ m~10 μ m, 0.5 μ m~5 μ m, 0.5 μ m~3 μ m, 0.8 μ m~100 μ m, 0.8 μ m~50 μ m, 0.8 μ m~10 μ m, 0.8 μ m~5 μ m, 0.8 μ m~3 μ m, 1 μ m~100μ m, 1 μ m~50 μ m, 1 μ m~10 μ m, 1 μ m~5 μ m or 1 μ m~3 μ The median particle size (D50 (median diameter), volume basis) of the antimicrobial metal-containing deodorant can be measured using a laser diffraction particle size distribution analyzer, and specifically, is a value measured by the method described in Examples.
[0030] In addition, if the BET specific surface area of the deodorant containing an antimicrobial metal is large, the frequency of contact between the antimicrobial metal and urease increases. On the other hand, the frequency of contact between the antimicrobial metal and L-cystine also increases. In addition, if the BET specific surface area of the deodorant containing an antimicrobial metal is too large, the dust generation rate may increase. In this case, the BET specific surface area of the porous deodorant is preferably 100 m 2 / g~2000m 2 / g、100m 2 / g~1500m 2 / g、100m 2 / g~1000m 2 / g、100m 2 / g~800m 2 / g、300m 2 / g~2000m 2 / g、300m 2 / g~1500m 2 / g、300m 2 / g~1000m 2 / g、300m 2 / g~800m 2 / g、500m 2 / g~2000m 2 / g、500m 2 / g~1500m 2 / g、500m 2 / g~1000m 2 / g or 500m 2 / g~800m 2 / g.
[0031] The BET specific surface area of the antimicrobial metal-containing deodorant can be measured using a specific surface area measuring device, and specifically, is a value measured by the method described in Examples.
[0032] The sum (x + y) of the content x (mass %) of the porous deodorant in the entire water-absorbent resin composition of the present invention and the content y (mass %) of the antimicrobial metal-containing deodorant is 0.10 mass % or more. From the viewpoint of more appropriately exhibiting the effects of the present invention, the sum (x + y) may be 0.10 mass % to 0.80 mass %, 0.10 mass % to 0.60 mass %, 0.10 mass % to 0.50 mass %, 0.10 mass % to 0.40 mass %, 0.10 mass % to 0.35 mass %, 0.10 mass % to 0.30 mass %, 0.13 mass % to 0.80 mass %, 0.13 mass % to 0.60 mass %, 0. 13 mass% to 0.50 mass%, 0.13 mass% to 0.40 mass%, 0.13 mass% to 0.35 mass%, 0.13 mass% to 0.30 mass%, 0.18 mass% to 0.80 mass%, 0.18 mass% to 0.60 mass%, 0.18 mass% to 0.50 mass%, 0.18 mass% to 0.40 mass%, 0.18 mass% to 0.35 mass%, 0.18 mass% to 0.30 mass%, 0 .20 mass% to 0.80 mass%, 0.20 mass% to 0.60 mass%, 0.20 mass% to 0.50 mass%, 0.20 mass% to 0.40 mass%, 0.20 mass% to 0.35 mass%, 0.20 mass% to 0.30 mass%, 0.25 mass% to 0.80 mass%, 0.25 mass% to 0.60 mass%, 0.25 mass% to 0.50 mass%, 0.25 mass% to 0.40 mass%, 0.25% to 0.35% by mass, 0.25% to 0.30% by mass, 0.30% to 0.80% by mass, 0.30% to 0.60% by mass, 0.30% to 0.50% by mass, 0.30% to 0.40% by mass, 0.35% to 0.80% by mass, 0.35% to 0.60% by mass, 0.35% to 0.50% by mass, or 0.35% to 0.40% by mass. It should be noted that if the sum (x + y) of the content x (mass %) of the porous deodorant and the content y (mass %) of the antimicrobial metal-containing deodorant is large, the dust generation rate increases, which may reduce the handling properties of the water-absorbent resin composition. Considering this dust generation rate, the sum (x + y) is preferably 0.50% by mass or less.
[0033] Furthermore, from the viewpoint of more appropriately exhibiting the effects of the present invention, the content y (mass %) of the antimicrobial metal-containing deodorant in the entire water-absorbent resin composition of the present invention may be 0.020% by mass to 0.12% by mass, 0.020% by mass to 0.08% by mass, 0.020% by mass to 0.06% by mass, 0.020% by mass to 0.04% by mass, 0.024% by mass to 0.12% by mass, 0.024% by mass to 0.08% by mass, 0.024% by mass to 0.06% by mass, 0.024% by mass to 0.04% by mass, 0.028% by mass to 0.12% by mass, 0.028% by mass to 0.08% by mass, 0.028% by mass to 0.06% by mass, 0.028% by mass to 0.04% by mass, 0.05% by mass to 0.12% by mass, 0.05% by mass to 0.08% by mass, or 0.05% by mass to 0.06% by mass.
[0034] In addition, the ratio (X / Y) of the content X (parts by mass) of the porous deodorant in the water-absorbing resin composition of the present invention to the content Y (parts by mass) of the antimicrobial metal-containing deodorant is 0.8 or greater. From the perspective of more appropriately exhibiting the effects of the present invention, the ratio (X / Y) may be 0.8-15.0, 0.8-12.0, 0.8-10.0, 0.8-8.0, 0.8-5.0, 1.0-15.0, 1.0-12.0, 1.0-10.0, 1.0-8.0, 1.0-5.0, 2.0-15.0, 2.0-12.0, 2.0-10.0, 2.0-8.0, 2.0-5.0, 3.0-15.0, 3.0-12.0, 3.0-10.0, 3.0-8.0, or 3.0-5.0.
[0035] As described above, in the water-absorbent resin composition of the present invention, the antimicrobial metal-containing deodorant can be disposed on the surface of the water-absorbent polymer particles (i.e., the antimicrobial metal-containing deodorant is present on the surface of the water-absorbent polymer particles). For example, by mixing the water-absorbent polymer particles with the particulate antimicrobial metal-containing deodorant in a solid phase, the antimicrobial metal-containing deodorant adheres to the surface of the water-absorbent polymer particles, thereby disposing the antimicrobial metal-containing deodorant on the surface of the water-absorbent polymer particles.
[0036] (Porous deodorant) Porous deodorants are porous and contain substantially no antimicrobial metals. Here, "deodorants containing substantially no antimicrobial metals" include deodorants containing antimicrobial metals to the extent that they do not exhibit substantial antimicrobial properties, as well as deodorants containing no antimicrobial metals at all, for example, deodorants containing less than 1% by mass of antimicrobial metals.
[0037] To more effectively achieve the effects of the present invention, the porous deodorant may contain at least one selected from activated carbon, silicon dioxide, and silicates, or may contain at least one of activated carbon and silicon dioxide. In particular, since an excellent adsorption effect for L-cystine can be expected, the porous deodorant preferably contains at least activated carbon, with the proportion (mass %) being, for example, 80% to 100% by mass, 90% to 100% by mass, or 95% to 100% by mass.
[0038] From the viewpoint of more appropriately exerting the effects of the present invention, the median particle size of the porous deodorant may be 1 μ m~100 μ m, 1 μ m~80 μ m, 1 μ m~60 μ m, 10 μ m~100 μ m, 10 μ m~80 μ m, 10 μ m~60 μ m, 15 μ m~100 μ m, 15 μ m~80 μ m, 15 μ m~60 μ m, 20 μ m~100 μ m, 20 [[ID= m~80 m or 20 m~60 m.
[0039] The median particle size (D50 (median diameter), volume basis) of the porous deodorant can be measured using a laser diffraction particle size distribution analyzer, and specifically, is a value measured by the method described in Examples.
[0040] From the viewpoint of more appropriately exhibiting the effects of the present invention, the shape of the porous deodorant is preferably a crushed shape, a cylindrical shape, or the like, and more preferably a crushed shape.
[0041] In addition, from the viewpoint of more appropriately exerting the effects of the present invention, the BET specific surface area of the porous deodorant may be 100 m 2 / g~3000m 2 / g、100m 2 / g~2500m 2 / g、100m 2 / g~2000m 2 / g、100m2 / g~1500m 2 / g、500m 2 / g~3000m 2 / g、500m 2 / g~2500m 2 / g、500m 2 / g~2000m 2 / g、500m 2 / g~1500m 2 / g、1000m 2 / g~3000m 2 / g、1000m 2 / g~2500m 2 / g、1000m 2 / g~2000m 2 / g or 1000m 2 / g~1500m 2 / g. If the BET specific surface area of the porous deodorant is large, L-cystine contained in urine can be efficiently adsorbed. On the other hand, if the BET specific surface area of the porous deodorant is too large, each pore becomes finer, thereby reducing the strength of the porous deodorant and possibly increasing the dust generation rate. Therefore, the upper limit of the BET specific surface area is preferably 2000 m 2 / g.
[0042] The BET specific surface area of the porous deodorant can be measured using a specific surface area measuring device, and specifically, is a value measured by the method described in Examples.
[0043] From the perspective of more effectively demonstrating the effects of the present invention, the activated carbon used as the porous deodorant is preferably one having polar functional groups (hydrophilic functional groups) on its surface (i.e., hydrophilic activated carbon). Examples of polar functional groups include hydroxyl groups, carboxyl groups, and phenolic groups. Activated carbon having polar functional groups on its surface is commercially available, for example, as liquid phase activated carbon and water treatment activated carbon.
[0044] Examples of sources for activated carbon include coconut shells, infusible or carbonized organic materials, and infusible resins such as phenolic resins. Examples of organic materials include polyacrylonitrile, asphalt, polyvinyl alcohol, and cellulose. Among these, preferred sources for activated carbon are wood (sawdust), coconut shells, and asphalt (e.g., coal tar).
[0045] From the viewpoint of more appropriately exhibiting the effects of the present invention, the content rate x (mass %) of the porous deodorant in the water-absorbent resin composition of the present invention may be, for example, 0.05% by mass to 0.40% by mass, 0.05% by mass to 0.35% by mass, 0.05% by mass to 0.30% by mass, 0.08% by mass to 0.40% by mass, 0.08% by mass to 0.35% by mass, 0.08% by mass to 0.30% by mass, 0.10% by mass to 0.4 ...08% by mass to 0.35% by mass, 0.08% by mass to 0.30% by mass, 0.10% by mass to 0.40% by mass, 0.08% by mass to 0.35% by mass, 0.08% by mass to 0.30% by mass, 0.10% by mass to 0.40% by mass, 0.08% by mass to 0.35% by mass, 0.08% by mass to 0 % to 0.35 mass%, 0.10 mass% to 0.30 mass%, 0.15 mass% to 0.40 mass%, 0.15 mass% to 0.35 mass%, 0.15 mass% to 0.30 mass%, 0.20 mass% to 0.40 mass%, 0.20 mass% to 0.35 mass%, 0.20 mass% to 0.30 mass%, 0.25 mass% to 0.40 mass%, 0.25 mass% to 0.35 mass%, or 0.25 mass% to 0.30 mass%.
[0046] The iodine adsorption amount of the porous deodorant may be, for example, 100 mg / g to 3000 mg / g, 100 mg / g to 2000 mg / g, 500 mg / g to 3000 mg / g, or 500 mg / g to 2000 mg / g.
[0047] Here, the iodine adsorption amount of activated carbon refers to a value measured in accordance with JIS K1474:2014.
[0048] When the porous deodorant has a low loss on drying (in other words, a high purity of the porous deodorant), the deodorizing effect is more effective, but on the other hand, there is a tendency to generate dust. Taking this into account, the loss on drying of the porous deodorant can be, for example, 0.1% to 15.0%, 0.1% to 10.0%, 0.1% to 5.0%, 0.5% to 15.0%, 0.5% to 10.0%, 0.5% to 5.0%, 1.0% to 15.0%, 1.0% to 10.0%, or 1.0% to 5.0%.
[0049] Here, the loss on drying of the porous deodorant refers to a value measured in accordance with JIS K1474:2014.
[0050] The pH of the porous deodorant may be, for example, 3.0 to 12.0, 3.0 to 11.0, 3.0 to 8.0, 3.0 to 5.0, 4.0 to 12.0, 4.0 to 11.0, 4.0 to 8.0, or 4.0 to 5.0.
[0051] Here, the pH of the porous deodorant refers to a value measured in accordance with JIS K1474:2014.
[0052] As described above, in the water-absorbent resin composition of the present invention, the porous deodorant can be disposed on the surface of the water-absorbent polymer particles (i.e., the porous deodorant is present on the surface of the water-absorbent polymer particles). For example, the porous deodorant can be disposed on the surface of the water-absorbent polymer particles by mixing the water-absorbent polymer particles and the porous deodorant in a solid phase so that the porous deodorant adheres to the surface of the water-absorbent polymer particles.
[0053] Next, the water-absorbing polymer particles (water-absorbing resin particles) contained in the water-absorbing resin composition of the present invention will be described in detail.
[0054] (Water-absorbent polymer particles) The water-absorbent polymer particles contained in the water-absorbent resin composition of the present invention are composed of a cross-linked polymer of a water-soluble ethylenically unsaturated monomer, that is, a cross-linked polymer having a structural unit derived from a water-soluble ethylenically unsaturated monomer.
[0055] From the viewpoint of suppressing urine absorption by the water-absorbing polymer particles before the porous deodorant has sufficiently absorbed L-cystine and ensuring practically sufficient water absorption performance, the water-absorbing polymer particles may have a water absorption rate as measured by a vortex method of, for example, 10 to 80 seconds, 10 to 60 seconds, 10 to 40 seconds, 20 to 80 seconds, 20 to 60 seconds, 20 to 40 seconds, 30 to 80 seconds, 30 to 60 seconds, or 30 to 40 seconds.
[0056] The water absorption rate of the water-absorbent polymer particles by the vortex method is a value measured by the method described in Examples.
[0057] The physiological saline water retention capacity of the water-absorbing polymer particles can be, for example, 20 g / g to 60 g / g, 20 g / g to 55 g / g, 20 g / g to 50 g / g, 25 g / g to 60 g / g, 25 g / g to 55 g / g, 25 g / g to 50 g / g, 30 g / g to 60 g / g, 30 g / g to 55 g / g, or 30 g / g to 50 g / g.
[0058] The water absorption of physiological saline under a load of 4.14 kPa by the water-absorbent polymer particles can be, for example, 10 mL / g to 40 mL / g, 10 mL / g to 35 mL / g, 10 mL / g to 30 mL / g, 13 mL / g to 40 mL / g, 13 mL / g to 35 mL / g, 13 mL / g to 30 mL / g, 15 mL / g to 40 mL / g, 15 mL / g to 35 mL / g, or 15 mL / g to 30 mL / g.
[0059] The physiological saline water retention capacity and the physiological saline water absorption capacity under a load of 4.14 kPa of the water-absorbent polymer particles are values measured by the methods described in Examples.
[0060] The median particle size of the water-absorbing polymer particles can be, for example, 150 m~850 m, 150 m~600 m, 150 m~550 m, 150 m~500 m, 150 m~450 m, 150 m~400 m, 200 m~850 m, 200 m~600 m, 200 m~550 m, 200 m~500 m, 200 m~450 m, 200 m~400 m, 240 m~850 m, 240 m~600 m, 240 m~550 m, 240 m~500 m, 240 m~450 m, 240 m~400 m, 260 m~850 m, 260 m~600 m, 260 m~550 m, 260 m~500 m, 260 m~450 m, 260 m~400 m, 280 m~850 m, 280 m~600 m, 280 m~550 m, 280 m~500 m, 280 m~450 m, 280 m~400 m, 300 m~850 m, 300 m~600 m, 300 m~550 m, 300 m~500 m, 300 m~450 m or 300 m~400 m.
[0061] In addition to being composed of single particles, the water-absorbing polymer particles may also be in the form of aggregates of fine particles (primary particles) (secondary particles). Examples of primary particle shapes include roughly spherical shapes, irregularly shaped fragments, and plate-like shapes. In the case of primary particles produced by reversed-phase suspension polymerization, examples include roughly spherical single particles with smooth surface shapes such as true spheres and ellipsoids.
[0062] The median particle size of the water-absorbing polymer particles can be measured using a JIS standard sieve, and specifically, is a value measured by the method described in Examples.
[0063] Representative polymerization methods for water-soluble ethylenically unsaturated monomers include aqueous solution polymerization, emulsion polymerization, and reversed-phase suspension polymerization. In aqueous solution polymerization, polymerization is carried out by heating an aqueous solution of a water-soluble ethylenically unsaturated monomer while stirring as needed. Alternatively, in reversed-phase suspension polymerization, polymerization is carried out by heating a water-soluble ethylenically unsaturated monomer in a hydrocarbon dispersion medium while stirring.
[0064] An example of a method for producing the water-absorbing polymer particles will be described below.
[0065] A specific example of a method for producing water-absorbent polymer particles includes a method for producing water-absorbent polymer particles by reverse-phase suspension polymerization of a water-soluble ethylenically unsaturated monomer in a hydrocarbon dispersion medium, comprising a polymerization step in the presence of a free radical polymerization initiator and a surface crosslinking step of the resulting hydrogel in the presence of a surface crosslinking agent. In the method for producing water-absorbent polymer particles of the present invention, an internal crosslinking agent may be added to the water-soluble ethylenically unsaturated monomer, if desired, to produce a hydrogel having an internally crosslinked structure.
[0066] <Polymerization process> [Water-soluble ethylenically unsaturated monomer] Examples of water-soluble ethylenically unsaturated monomers include (meth)acrylic acid (in this specification, "acrylic acid" and "methacrylic acid" are collectively referred to as "(meth)acrylic acid"; the same shall apply hereinafter) and its salts; 2-(meth)acrylamide-2-methylpropanesulfonic acid and its salts; nonionic monomers such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, 2-hydroxyethyl(meth)acrylate, N-hydroxymethyl(meth)acrylamide, and polyethylene glycol mono(meth)acrylate; and amino group-containing unsaturated monomers such as N,N-diethylaminoethyl(meth)acrylate, N,N-diethylaminopropyl(meth)acrylate, and diethylaminopropyl(meth)acrylamide, and their quaternized products. Among these water-soluble ethylenically unsaturated monomers, (meth)acrylic acid or its salts, (meth)acrylamide, and N,N-dimethylacrylamide are preferred, with (meth)acrylic acid and its salts being more preferred due to their industrial availability. In addition, these water-soluble ethylenically unsaturated monomers may be used alone or in combination of two or more.
[0067] Among them, acrylic acid and its salts are widely used as raw materials for water-absorbing polymer particles. These acrylic acid and / or its salts may also be used by copolymerizing with other water-soluble ethylenically unsaturated monomers as described above. In such cases, acrylic acid and / or its salts are preferably used as the main water-soluble ethylenically unsaturated monomer in an amount of 70 to 100 mol % relative to the total water-soluble ethylenically unsaturated monomers.
[0068] The water-soluble ethylenically unsaturated monomer can be dispersed in a hydrocarbon dispersion medium in the form of an aqueous solution and provided for reverse suspension polymerization. By forming an aqueous solution, the water-soluble ethylenically unsaturated monomer can improve the dispersion efficiency in the hydrocarbon dispersion medium. The concentration of the water-soluble ethylenically unsaturated monomer in the aqueous solution is preferably in the range of 20% by mass to below the saturation concentration. In addition, the concentration of the water-soluble ethylenically unsaturated monomer is more preferably 55% by mass or less, further preferably 50% by mass or less, and even more preferably 45% by mass or less. On the other hand, the concentration of the water-soluble ethylenically unsaturated monomer is more preferably 25% by mass or more, further preferably 28% by mass or more, and even more preferably 30% by mass or more.
[0069] When a water-soluble ethylenically unsaturated monomer has an acid group, such as (meth)acrylic acid or 2-(meth)acrylamide-2-methylpropanesulfonic acid, the acid group may be pre-neutralized with an alkaline neutralizing agent, as needed. Examples of such alkaline neutralizing agents include alkali metal salts such as sodium hydroxide, sodium carbonate, sodium bicarbonate, potassium hydroxide, and potassium carbonate; and ammonia. Furthermore, to simplify the neutralization process, these alkaline neutralizing agents may be used in the form of aqueous solutions. These alkaline neutralizing agents may be used alone or in combination of two or more.
[0070] The degree of neutralization of the water-soluble ethylenically unsaturated monomer with the alkaline neutralizing agent is preferably 10 mol % to 100 mol %, more preferably 30 mol % to 90 mol %, further preferably 40 mol % to 85 mol %, and even more preferably 50 mol % to 80 mol %, relative to all acid groups of the water-soluble ethylenically unsaturated monomer.
[0071] [Free radical polymerization initiator] Examples of the radical polymerization initiator added in the polymerization step include persulfates such as potassium persulfate, ammonium persulfate, and sodium persulfate; peroxides such as methyl ethyl ketone peroxide, methyl isobutyl ketone peroxide, di-tert-butyl peroxide, tert-butyl isopropyl benzene peroxide, tert-butyl peroxyacetate, tert-butyl peroxyisobutyrate, tert-butyl peroxypivalate, and hydrogen peroxide; and 2,2′-azobis(2-amidinopropane) dihydrochloride, 2,2′-azobis[2-(N-phenylamidino)propane] Azo compounds such as dihydrochloride, 2,2′-azobis[2-(N-allylamidino)propane] dihydrochloride, 2,2′-azobis{2-[1-(2-hydroxyethyl)-2-imidazolin-2-yl]propane} dihydrochloride, 2,2′-azobis{2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide}, 2,2′-azobis[2-methyl-N-(2-hydroxyethyl)-propionamide], and 4,4′-azobis(4-cyanovaleric acid) are preferred. Among these free radical polymerization initiators, potassium persulfate, ammonium persulfate, sodium persulfate, and 2,2′-azobis(2-amidinopropane) dihydrochloride are preferred due to their ease of availability and handling. These free radical polymerization initiators can be used alone or in combination of two or more. Furthermore, the above-mentioned radical polymerization initiator can also be used in combination with a reducing agent such as sodium sulfite, sodium bisulfite, ferrous sulfate, and L-ascorbic acid to be used as a redox polymerization initiator.
[0072] The amount of the radical polymerization initiator used is, for example, 0.00005 mol to 0.01 mol per mol of the water-soluble ethylenically unsaturated monomer. This amount can avoid a violent polymerization reaction and allow the polymerization reaction to be completed within a suitable time.
[0073] [Internal crosslinking agent] Examples of the internal crosslinking agent include crosslinking agents capable of crosslinking the polymer of the water-soluble ethylenically unsaturated monomer used, such as unsaturated polyesters obtained by reacting diols, triols, and other polyols such as (poly)ethylene glycol ["(poly)" refers to both the case with the prefix "poly" and the case without the prefix "poly". The same shall apply hereinafter), (poly)propylene glycol, 1,4-butanediol, 1,6-hexanediol, trimethylolpropane, and (poly)glycerol with unsaturated acids such as (meth)acrylic acid, maleic acid, and fumaric acid; bisacrylamides such as N,N-methylenebisacrylamide; di(meth)acrylates or tri(meth)acrylates obtained by reacting polyepoxide with (meth)acrylic acid; and polyisocyanates such as toluene diisocyanate and hexamethylene diisocyanate with Di(meth)acrylate carbamoyl esters obtained by reacting hydroxyethyl(meth)acrylate; compounds having two or more polymerizable unsaturated groups such as allyl starch, allylated cellulose, diallyl phthalate, N,N',N''-triallyl isocyanurate, and divinylbenzene; diglycidyl compounds such as (poly)ethylene glycol diglycidyl ether, (poly)propylene glycol diglycidyl ether, and (poly)glycerol diglycidyl ether, triglycidyl compounds, and other polyglycidyl compounds; epichlorohydrin, epibromohydrin, α Epihalohydrin compounds such as methylepichlorohydrin; compounds having two or more reactive functional groups, such as isocyanate compounds such as 2,4-toluene diisocyanate and hexamethylene diisocyanate; and oxetane compounds such as 3-methyl-3-hydroxymethyloxetane, 3-ethyl-3-hydroxymethyloxetane, 3-butyl-3-hydroxymethyloxetane, 3-methyl-3-hydroxyethyloxetane, 3-ethyl-3-hydroxyethyloxetane, and 3-butyl-3-hydroxyethyloxetane. Among these internal crosslinking agents, polyglycidyl compounds are preferred, and diglycidyl ether compounds are more preferred, with (poly)ethylene glycol diglycidyl ether, (poly)propylene glycol diglycidyl ether, and (poly)glycerol diglycidyl ether being preferred. These internal crosslinking agents can be used alone or in combination of two or more.
[0074] The amount of the internal crosslinking agent used is preferably 0.000001 mol to 0.02 mol, more preferably 0.00001 mol to 0.01 mol, further preferably 0.00001 mol to 0.005 mol, and even more preferably 0.00005 mol to 0.002 mol, based on 1 mol of the water-soluble ethylenically unsaturated monomer.
[0075] [Hydrocarbon dispersion medium] Examples of hydrocarbon dispersion media include aliphatic hydrocarbons with 6 to 8 carbon atoms, such as n-hexane, n-heptane, 2-methylhexane, 3-methylhexane, 2,3-dimethylpentane, 3-ethylpentane, and n-octane; alicyclic hydrocarbons, such as cyclohexane, methylcyclohexane, cyclopentane, methylcyclopentane, trans-1,2-dimethylcyclopentane, cis-1,3-dimethylcyclopentane, and trans-1,3-dimethylcyclopentane; and aromatic hydrocarbons, such as benzene, toluene, and xylene. Of these hydrocarbon dispersion media, n-hexane, n-heptane, and cyclohexane are particularly preferred due to their industrial availability, stable quality, and low cost. These hydrocarbon dispersion media can be used alone or in combination of two or more. Suitable results can also be achieved using commercially available products such as Exxsol Heptane (manufactured by ExxonMobil Corporation: hydrocarbons containing 75% to 85% by mass of heptane and its isomers) as an example of a mixture of hydrocarbon dispersion media.
[0076] The amount of the hydrocarbon dispersion medium used is preferably 100 to 1500 parts by mass, and more preferably 200 to 1400 parts by mass, relative to 100 parts by mass of the water-soluble ethylenically unsaturated monomer in the first stage, from the perspective of uniformly dispersing the water-soluble ethylenically unsaturated monomer and facilitating polymerization temperature control. As described below, reversed-phase suspension polymerization is carried out in a single stage (single stage) or in multiple stages of two or more. The first stage polymerization described above refers to the first stage polymerization reaction in the single stage polymerization or multistage polymerization (the same applies hereinafter).
[0077] [Dispersion stabilizer] (Surfactant) In reversed-phase suspension polymerization, a dispersion stabilizer may be used to improve the dispersion stability of the water-soluble ethylenically unsaturated monomer in the hydrocarbon dispersion medium.
[0078] As surfactant, for example, sucrose fatty acid ester, polyglycerol fatty acid ester, sorbitan fatty acid ester, polyoxyethylene sorbitan fatty acid ester, polyoxyethylene glycerol fatty acid ester, sorbitol fatty acid ester, polyoxyethylene sorbitol fatty acid ester, polyoxyethylene alkyl ether, polyoxyethylene alkylphenyl ether, polyoxyethylene castor oil, polyoxyethylene hydrogenated castor oil, alkyl allyl formaldehyde condensation polyoxyethylene ether, polyoxyethylene polyoxypropylene block copolymer, polyoxyethylene polyoxypropylene alkyl ether, polyethylene glycol fatty acid ester, alkyl glucoside, N-alkyl glucamide, polyoxyethylene fatty acid amide, polyoxyethylene alkylamine, the phosphoric acid ester of polyoxyethylene alkyl ether, the phosphoric acid ester of polyoxyethylene alkyl allyl ether etc. can be used. Among these surfactants, from the dispersion stability aspect of monomer, particularly preferably use sorbitan fatty acid ester, polyglycerol fatty acid ester, sucrose fatty acid ester. These surfactants can be used alone, and two or more can also be used in combination.
[0079] The amount of the surfactant used is preferably 0.1 to 30 parts by mass, more preferably 0.3 to 20 parts by mass, relative to 100 parts by mass of the water-soluble ethylenically unsaturated monomer in the first stage.
[0080] (Polymer dispersant) Furthermore, as a dispersion stabilizer used in reversed-phase suspension polymerization, a polymeric dispersant may be used together with the above-mentioned surfactant.
[0081] Examples of polymeric dispersants include maleic anhydride-modified polyethylene, maleic anhydride-modified polypropylene, maleic anhydride-modified ethylene-propylene copolymer, maleic anhydride-modified EPDM (ethylene-propylene-diene terpolymer), maleic anhydride-modified polybutadiene, maleic anhydride-ethylene copolymer, maleic anhydride-propylene copolymer, maleic anhydride-ethylene-propylene copolymer, maleic anhydride-butadiene copolymer, polyethylene, polypropylene, ethylene-propylene copolymer, oxidized polyethylene, oxidized polypropylene, oxidized ethylene-propylene copolymer, ethylene-acrylic acid copolymer, ethyl cellulose, ethyl hydroxyethyl cellulose, etc. Among these polymeric dispersants, maleic anhydride-modified polyethylene, maleic anhydride-modified polypropylene, maleic anhydride-modified ethylene-propylene copolymer, maleic anhydride-ethylene copolymer, maleic anhydride-propylene copolymer, maleic anhydride-ethylene-propylene copolymer, polyethylene, polypropylene, ethylene-propylene copolymer, oxidized polyethylene, oxidized polypropylene, and oxidized ethylene-propylene copolymer are particularly preferably used from the perspective of monomer dispersion stability. These polymeric dispersants may be used alone or in combination of two or more.
[0082] The amount of the polymeric dispersant used is preferably 0.1 to 30 parts by mass, more preferably 0.3 to 20 parts by mass, relative to 100 parts by mass of the water-soluble ethylenically unsaturated monomer in the first stage.
[0083] [Other ingredients] In the method for producing water-absorbing polymer particles, other components may be added to the aqueous solution containing the water-soluble ethylenically unsaturated monomer as needed to carry out reversed-phase suspension polymerization. Various additives such as thickeners and chain transfer agents may be added as other components.
[0084] For example, a thickener may be added to an aqueous solution containing a water-soluble ethylenically unsaturated monomer to perform reversed-phase suspension polymerization. By adding a thickener, the viscosity of the aqueous solution is adjusted, and the median particle size obtained in the reversed-phase suspension polymerization can be controlled.
[0085] Examples of thickeners that can be used include hydroxyethyl cellulose, hydroxypropyl cellulose, methyl cellulose, carboxymethyl cellulose, polyacrylic acid, (partially) neutralized polyacrylic acid, polyethylene glycol, polyacrylamide, polyethyleneimine, dextrin, sodium alginate, polyvinyl alcohol, polyvinyl pyrrolidone, and polyethylene oxide. It should be noted that, at the same stirring rate during polymerization, the higher the viscosity of the aqueous solution of the water-soluble ethylenically unsaturated monomer, the larger the primary and / or secondary particles of the resulting particles tend to be.
[0086] [Inverse Phase Suspension Polymerization] In reversed-phase suspension polymerization, for example, an aqueous monomer solution containing a water-soluble ethylenically unsaturated monomer is dispersed in a hydrocarbon dispersion medium in the presence of a dispersion stabilizer. In this case, the dispersion stabilizer (surfactant, polymeric dispersant) can be added either before or after the addition of the aqueous monomer solution, provided it is before the start of the polymerization reaction.
[0087] Among them, from the viewpoint of easily reducing the amount of hydrocarbon dispersion medium remaining in the obtained water-absorbing polymer particles, it is preferred to disperse the monomer aqueous solution in a hydrocarbon dispersion medium containing a polymeric dispersant and then further disperse a surfactant before polymerization.
[0088] Such reversed-phase suspension polymerization can be carried out in one stage or in multiple stages of two or more stages. However, from the viewpoint of improving productivity, it is preferably carried out in two to three stages.
[0089] Under the situation of carrying out reversed-phase suspension polymerization with the multistage more than two stages, after carrying out the reversed-phase suspension polymerization of the first stage, in the reaction mixture obtained by the polyreaction of the first stage, add water-soluble ethylenically unsaturated monomers and mix, carry out the reversed-phase suspension polymerization after the second stage with the method identical with the first stage.In the reversed-phase suspension polymerization in each stage after the second stage, preferably except water-soluble ethylenically unsaturated monomers, the amount of the water-soluble ethylenically unsaturated monomers that free radical polymerization initiator adds during the reversed-phase suspension polymerization in each stage after the second stage is as benchmark, in the scope of the mol ratio of above-mentioned each composition relative to water-soluble ethylenically unsaturated monomers, add, carry out reversed-phase suspension polymerization.Should be explained, in the polymerization after the second stage, as required, also internal crosslinking agent can be added in the water-soluble ethylenically unsaturated monomers.
[0090] The reaction temperature of the polymerization reaction is preferably 20° C. to 110° C., more preferably 40° C. to 90° C., from the viewpoints of rapidly progressing the polymerization and shortening the polymerization time to improve economic efficiency, and easily removing the polymerization heat to smoothly progress the reaction.
[0091] Surface cross-linking process Next, the water-absorbent polymer particles of the present invention are obtained by adding a surface crosslinking agent to a hydrogel having an internally crosslinked structure obtained by polymerizing a water-soluble ethylenically unsaturated monomer, and crosslinking the resultant (surface crosslinking reaction). This surface crosslinking reaction is preferably performed in the presence of the surface crosslinking agent after the polymerization of the water-soluble ethylenically unsaturated monomer has completed. By subjecting the hydrogel having an internally crosslinked structure to a surface crosslinking reaction after polymerization, the crosslink density near the surface of the water-absorbent polymer particles can be increased, resulting in water-absorbent polymer particles having improved properties such as water absorption under load.
[0092] Examples of surface crosslinking agents include compounds having two or more reactive functional groups. Examples include: polyols such as ethylene glycol, propylene glycol, 1,4-butanediol, diethylene glycol, triethylene glycol, trimethylolpropane, glycerol, polyoxyethylene glycol, polyoxypropylene glycol, and polyglycerol; polyglycidyl compounds such as (poly)ethylene glycol diglycidyl ether, (poly)glycerol diglycidyl ether, (poly)glycerol triglycidyl ether, trimethylolpropane triglycidyl ether, (poly)propylene glycol polyglycidyl ether, and (poly)glycerol polyglycidyl ether; and epichlorohydrin, epibromohydrin, α Halogenated epoxy compounds such as methyl epichlorohydrin; isocyanate compounds such as 2,4-toluene diisocyanate and hexamethylene diisocyanate; oxetane compounds such as 3-methyl-3-hydroxymethyloxetane, 3-ethyl-3-hydroxymethyloxetane, 3-butyl-3-hydroxymethyloxetane, 3-methyl-3-hydroxyethyloxetane, 3-ethyl-3-hydroxyethyloxetane, and 3-butyl-3-hydroxyethyloxetane; oxazoline compounds such as 1,2-ethylenebisoxazoline; ethylene carbonate Carbonate compounds (such as alkylene carbonate) such as esters, propylene carbonate, 4,5-dimethyl-1,3-dioxolane-2-one, 4,4-dimethyl-1,3-dioxolane-2-one, 4-ethyl-1,3-dioxolane-2-one, 4-hydroxymethyl-1,3-dioxolane-2-one, 1,3-dioxane-2-one, 4-methyl-1,3-dioxane-2-one, 4,6-dimethyl-1,3-dioxane-2-one, and 1,3-dioxane-2-one; bis[N,N-di( β
[0014] Hydroxyalkylamide compounds such as (-hydroxyethyl)] adipamide. Among these surface crosslinking agents, polyglycidyl compounds such as (poly)ethylene glycol diglycidyl ether, (poly)glycerol diglycidyl ether, (poly)glycerol triglycidyl ether, trimethylolpropane triglycidyl ether, (poly)propylene glycol polyglycidyl ether, and (poly)glycerol polyglycidyl ether are preferred. These surface crosslinking agents may be used alone or in combination of two or more.
[0093] The amount of the surface crosslinking agent used is preferably 0.00001 to 0.01 mol, more preferably 0.00005 to 0.005 mol, and even more preferably 0.0001 to 0.002 mol, based on 1 mol of the total amount of the water-soluble ethylenically unsaturated monomer used in the polymerization.
[0094] The surface crosslinking agent can be added as is or as an aqueous solution. Alternatively, it can be added as a solution containing a hydrophilic organic solvent as needed. Examples of hydrophilic organic solvents include lower alcohols such as methanol, ethanol, n-propanol, and isopropanol; ketones such as acetone and methyl ethyl ketone; ethers such as diethyl ether, dioxane, and tetrahydrofuran; amides such as N,N-dimethylformamide; and sulfoxides such as dimethyl sulfoxide. These hydrophilic organic solvents can be used alone, in combination of two or more, or as a mixed solvent with water.
[0095] The surface crosslinking agent can be added after the polymerization reaction of the water-soluble ethylenically unsaturated monomer has substantially completely completed. The surface crosslinking agent is preferably added in the presence of 1 to 400 parts by mass of water, more preferably 5 to 200 parts by mass, further preferably 10 to 100 parts by mass, and even more preferably 20 to 60 parts by mass, relative to 100 parts by mass of the water-soluble ethylenically unsaturated monomer. The amount of water refers to the total amount of water contained in the reaction system and water used as needed when adding the surface crosslinking agent.
[0096] The reaction temperature in the surface cross-linking reaction is preferably 50° C. to 250° C., more preferably 60° C. to 180° C., even more preferably 60° C. to 140° C., and even more preferably 70° C. to 120° C. The reaction time for the surface cross-linking reaction is preferably 1 minute to 300 minutes, more preferably 5 minutes to 200 minutes.
[0097] <Drying process> After the reversed-phase suspension polymerization, a drying step may be included to remove water, the hydrocarbon dispersion medium, and the like by distillation using external application of energy such as heat. When dehydrating the hydrogel after reversed-phase suspension polymerization, the system containing the hydrogel dispersed in the hydrocarbon dispersion medium is heated to temporarily remove the water and hydrocarbon dispersion medium from the system by azeotropic distillation. In this case, continuous azeotropic distillation can be performed by returning only the distilled hydrocarbon dispersion medium to the system. This method maintains the temperature of the system during drying below the azeotropic temperature of the hydrocarbon dispersion medium, which is preferable from the perspective of minimizing resin degradation. Subsequently, the water and hydrocarbon dispersion medium are distilled off to obtain water-absorbing polymer particles. By controlling the treatment conditions in this post-polymerization drying step and adjusting the amount of water removed, the properties of the resulting water-absorbing polymer particles can be controlled.
[0098] In the drying step, the drying treatment by distillation can be carried out under normal pressure or under reduced pressure. In addition, from the viewpoint of improving the drying efficiency, it can also be carried out under a stream of nitrogen or the like. When the drying treatment is carried out under normal pressure, the drying temperature is preferably 70°C to 250°C, more preferably 80°C to 180°C, further preferably 80°C to 140°C, and even more preferably 90°C to 130°C. In addition, when the drying treatment is carried out under reduced pressure, the drying temperature is preferably 40°C to 160°C, more preferably 50°C to 110°C.
[0099] It should be noted that, when a surface crosslinking step using a surface crosslinking agent is performed after polymerization of the monomers by reversed-phase suspension polymerization, the drying step using distillation described above is performed after completion of the surface crosslinking step. Alternatively, the surface crosslinking step and the drying step may be performed simultaneously.
[0100] The water-absorbent resin composition of the present invention may contain additives depending on the intended purpose. Examples of such additives include inorganic powders, surfactants, oxidants, reducing agents, metal chelating agents, free radical chain inhibitors, antioxidants, and antimicrobial agents. For example, by adding 0.05 to 5 parts by mass of amorphous silica as an inorganic powder per 100 parts by mass of the water-absorbent polymer particles, the fluidity of the water-absorbent resin composition can be further improved. These additives are preferably hydrophilic or water-soluble.
[0101] In the water-absorbent resin composition of the present invention, the content of the water-absorbent polymer particles (excluding additives) is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more.
[0102] The water-absorbent resin composition of the present invention can be produced by, for example, mixing water-absorbent polymer particles, a particulate antimicrobial metal-containing deodorant, and a porous deodorant in a solid phase state.
[0103] The water-absorbent resin composition of the present invention is suitable for use in absorbent bodies used in absorbent articles such as sanitary products and diapers. The absorbent article of the present invention comprises an antimicrobial metal-containing deodorant, a porous deodorant, and water-absorbent polymer particles. The ratio (X / Y) of the porous deodorant content (X, parts by mass) to the antimicrobial metal-containing deodorant content (Y, parts by mass) is 0.8 or greater, and the sum (x + y) of the porous deodorant content (x, mass%) and the antimicrobial metal-containing deodorant content (y, mass%), based on the total amount of the antimicrobial metal-containing deodorant, the porous deodorant, and the water-absorbent polymer particles, is 0.10% or greater. The absorbent article of the present invention can have a more detailed structure similar to that of the water-absorbent resin composition described above.
[0104] Here, the absorbent body using the water-absorbent resin composition of the present invention comprises the particulate water-absorbent resin composition of the present invention. The absorbent body may further comprise hydrophilic fibers. Examples of absorbent body structures include sheet structures in which water-absorbent polymer particles are fixed to a nonwoven fabric or between multiple nonwoven fabrics; mixed dispersions obtained by mixing a particulate water-absorbent resin composition and hydrophilic fibers to achieve a uniform composition; sandwich structures in which a particulate water-absorbent resin composition is sandwiched between layers of hydrophilic fibers; and structures in which a particulate water-absorbent resin composition and hydrophilic fibers are wrapped in tissue paper. It should be noted that the absorbent body may contain other components, such as heat-fusible synthetic fibers, hot-melt adhesives, adhesives such as adhesive emulsions, etc., to improve the shape-retaining properties of the absorbent body.
[0105] The content of the water-absorbent resin composition in the absorbent body is preferably 5% by mass to 100% by mass, more preferably 10% by mass to 95% by mass, further preferably 20% by mass to 90% by mass, and even more preferably 30% by mass to 80% by mass.
[0106] Examples of hydrophilic fibers include cellulose fibers such as cotton pulp, mechanical pulp, chemical pulp, and semi-chemical pulp obtained from wood, man-made cellulose fibers such as rayon and cellulose acetate, and fibers made of hydrophilically treated synthetic resins such as polyamide, polyester, and polyolefin. The average fiber length of the hydrophilic fibers is generally 0.1 mm to 10 mm, or 0.5 mm to 5 mm.
[0107] The absorbent article of the present invention can be produced by holding an absorbent body using the particulate water-absorbent resin composition of the present invention between a liquid-permeable sheet (top sheet) and a liquid-impermeable sheet (back sheet). The liquid-permeable sheet is positioned on the side that contacts the body, and the liquid-impermeable sheet is positioned on the side opposite to the body.
[0108] Examples of liquid-permeable sheets include air-through, spunbond, chemically bonded, and needle-punched nonwoven fabrics made of fibers such as polyethylene, polypropylene, and polyester, as well as porous synthetic resin sheets. Examples of liquid-impermeable sheets include synthetic resin films made of resins such as polyethylene, polypropylene, and polyvinyl chloride.
[0109] This specification includes at least the inventions described in the following (1) to (14). (1) A water-absorbent resin composition comprising an antimicrobial metal-containing deodorant, a porous deodorant, and water-absorbent polymer particles, wherein the ratio (X / Y) of the content X (parts by mass) of the porous deodorant to the content Y (parts by mass) of the antimicrobial metal-containing deodorant is 0.8 or greater, and the sum (x + y) of the content x (mass %) of the porous deodorant and the content y (mass %) of the antimicrobial metal-containing deodorant in the entire water-absorbent resin composition is 0.10 mass % or greater. (2) The water-absorbent resin composition according to (1), wherein the sum (x+y) of the content x (mass %) and the content y (mass %) is 0.10% to 0.80% by mass, 0.10% to 0.60% by mass, 0.10% to 0.50% by mass, 0.10% to 0.40% by mass, 0.10% to 0.35% by mass, 0.10% to 0.30% by mass, 0.13% to 0.80% by mass, 0.13 mass% to 0.60 mass%, 0.13 mass% to 0.50 mass%, 0.13 mass% to 0.40 mass%, 0.13 mass% to 0.35 mass%, 0.13 mass% to 0.30 mass%, 0.18 mass% to 0.80 mass%, 0.18 mass% to 0.60 mass%, 0.18 mass% to 0.50 mass%, 0.18 mass% to 0.40 mass%, 0.18 mass% to 0.35 mass%, 0.18 mass% % to 0.30 mass%, 0.20 mass% to 0.80 mass%, 0.20 mass% to 0.60 mass%, 0.20 mass% to 0.50 mass%, 0.20 mass% to 0.40 mass%, 0.20 mass% to 0.35 mass%, 0.20 mass% to 0.30 mass%, 0.25 mass% to 0.80 mass%, 0.25 mass% to 0.60 mass%, 0.25 mass% to 0.50 mass%, 0.25 mass% to 0. % by mass, 0.40% by mass, 0.25% by mass to 0.35% by mass, 0.25% by mass to 0.30% by mass, 0.30% by mass to 0.80% by mass, 0.30% by mass to 0.60% by mass, 0.30% by mass to 0.50% by mass, 0.30% by mass to 0.40% by mass, 0.35% by mass to 0.80% by mass, 0.35% by mass to 0.60% by mass, 0.35% by mass to 0.50% by mass, or 0.35% by mass to 0.40% by mass. (3) The water-absorbing resin composition according to (1) or (2) above, wherein the antimicrobial metal contained in the antimicrobial metal-containing deodorant contains at least one selected from the group consisting of silver, copper, zinc, bismuth, cobalt, aluminum, and nickel. (4) The water-absorbing resin composition according to any one of (1) to (3) above, wherein the antimicrobial metal-containing deodorant comprises at least one selected from the group consisting of silver powder, silver (I) chloride, silver (I) oxide, and a substance carrying at least one metal ion of silver ion and zinc ion. (5) The water-absorbing resin composition according to any one of (1) to (4) above, wherein the porous deodorant contains at least one selected from the group consisting of activated carbon, silicon dioxide, and silicate. (6) The water-absorbing resin composition according to any one of (1) to (5), wherein the median particle size of the antimicrobial metal-containing deodorant is 0.1 m~100 m, the median particle size of the porous deodorant is 1 m~100 m. (7) The water-absorbing resin composition according to any one of (1) to (6), wherein the ratio (X / Y) of the content X (parts by mass) of the porous deodorant to the content Y (parts by mass) of the antimicrobial metal-containing deodorant is 0.8-15.0, 0.8-12.0, 0.8-10.0, 0.8-8.0, 0.8-5.0, 1.0-15.0, 1.0-12.0, 1.0-10.0, 1.0-8.0, 1.0-5.0, 2.0-15.0, 2.0-12.0, 2.0-10.0, 2.0-8.0, 2.0-5.0, 3.0-15.0, 3.0-12.0, 3.0-10.0, 3.0-8.0, or 3.0-5.0. (8) The water-absorbent resin composition according to any one of (1) to (7), wherein the water-absorbent polymer particles have a water absorption rate based on a vortex method of 10 to 80 seconds, 10 to 60 seconds, 10 to 40 seconds, 20 to 80 seconds, 20 to 60 seconds, 20 to 40 seconds, 30 to 80 seconds, 30 to 60 seconds, or 30 to 40 seconds. (9) An absorbent article comprising an antimicrobial metal-containing deodorant, a porous deodorant, and water-absorbent polymer particles, wherein the ratio (X / Y) of the content X (parts by mass) of the porous deodorant to the content Y (parts by mass) of the antimicrobial metal-containing deodorant is 0.8 or greater, and the sum (x + y) of the content x (mass %) of the porous deodorant and the content y (mass %) of the antimicrobial metal-containing deodorant, based on the total amount of the antimicrobial metal-containing deodorant, the porous deodorant, and the water-absorbent polymer particles, is 0.10 mass % or greater. (10) The absorbent article according to (9), wherein the sum (x+y) of the content x (mass %) and the content y (mass %) is 0.10% to 0.50% by mass, 0.10% to 0.40% by mass, 0.10% to 0.35% by mass, 0.10% to 0.30% by mass, 0.18% to 0.50% by mass, 0.18% to 0.40% by mass, 0.18% to 0.35% by mass, 0.18% to 0.30% by mass, 0.30% to 0.50% by mass, or 0.30% to 0.40% by mass. (11) The absorbent article according to (9) or (10), wherein the ratio (X / Y) of the content X (parts by mass) of the porous deodorant to the content Y (parts by mass) of the antibacterial metal-containing deodorant is 0.8-15.0, 0.8-12.0, 0.8-10.0, 0.8-8.0, 0.8-5.0, 1.0-15.0, 1.0-12.0, 1.0-10.0, 1.0-8.0, 1.0-5.0, 2.0-15.0, 2.0-12.0, 2.0-10.0, 2.0-8.0, 2.0-5.0, 3.0-15.0, 3.0-12.0, 3.0-10.0, 3.0-8.0, or 3.0-5.0. (12) The absorbent article according to any one of (9) to (11) above, wherein the antimicrobial metal-containing deodorant comprises at least one selected from the group consisting of silver powder, silver (I) chloride, silver (I) oxide, and a substance carrying at least one metal ion of silver ion and zinc ion. (13) The absorbent article according to any one of (9) to (12) above, wherein the porous deodorant contains at least one selected from the group consisting of activated carbon, silicon dioxide, and silicate. (14) The absorbent article according to any one of (9) to (13), wherein the water absorption rate of the water-absorbent polymer particles based on a vortex method is 10 to 80 seconds, 10 to 60 seconds, 10 to 40 seconds, 20 to 80 seconds, 20 to 60 seconds, 20 to 40 seconds, 30 to 80 seconds, 30 to 60 seconds, or 30 to 40 seconds.
[0124] Example The present invention will be described in detail below with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples.
[0125] The following water-absorbing polymer particles, activated carbon as a porous deodorant, and the water-absorbing resin compositions obtained in the Examples and Comparative Examples were evaluated using the following various tests. Unless otherwise specified, measurements were performed at a temperature of 25±2°C and a humidity of 50±10%.
[0126] [Production Example of Water-Absorbent Polymer Particles] A 2L, round-bottomed, cylindrical separable flask with an inner diameter of 11 cm and a volume was prepared, equipped with a reflux condenser, a dropping funnel, a nitrogen inlet tube, and a stirrer consisting of two stages of four inclined blades with a blade diameter of 5 cm. In this flask, 293 g of n-heptane as a hydrocarbon dispersion medium was added, along with 0.736 g of a maleic anhydride-modified ethylene-propylene copolymer (Mitsui Chemicals, Inc., HI-WAX1105A) as a polymeric dispersant. The mixture was heated to 80°C while stirring to dissolve the dispersant, and then cooled to 50°C. Separately, 92.0 g (1.03 mol) of an 80.5 mass % aqueous solution of acrylic acid as a water-soluble ethylenically unsaturated monomer was placed in a beaker with an internal volume of 300 mL. While cooling with ice water, 147.7 g of a 20.9 mass % aqueous solution of sodium hydroxide was added dropwise to neutralize the mixture to 75 mol %. Then, 0.092 g of hydroxyethyl cellulose (Sumitomo Seika Co., Ltd., HEC AW-15F) as a thickener, 0.0736 g (0.272 mmol) of potassium persulfate as a water-soluble free radical polymerization agent, and 0.010 g (0.057 mmol) of ethylene glycol diglycidyl ether as an internal crosslinking agent were added and dissolved to prepare a first-stage aqueous solution. The aqueous solution prepared above was then added to a separable flask and stirred for 10 minutes. A surfactant solution prepared by dissolving 0.736 g of HLB 3 sucrose stearate (Ryoto Sugar Ester S-370, Mitsubishi Chemical Foods Co., Ltd.) in 6.62 g of n-heptane by heating was then added to a 20 mL vial. While stirring at 550 rpm, the system was thoroughly purged with nitrogen. The flask was then immersed in a 70°C water bath, the temperature was raised, and polymerization was carried out for 60 minutes to obtain a first-stage polymerization slurry.
[0127] Meanwhile, in another beaker with an internal volume of 500 mL, 128.8 g (1.43 mol) of an 80.5 mass % aqueous solution of acrylic acid as a water-soluble ethylenically unsaturated monomer was taken and, while cooling with ice water, 159.0 g of a 27 mass % aqueous solution of sodium hydroxide was added dropwise. After 75 mol % neutralization, 0.103 g (0.381 mmol) of potassium persulfate as a water-soluble free radical polymerization initiator and 0.0117 g (0.067 mmol) of ethylene glycol diglycidyl ether as an internal crosslinking agent were added and dissolved to prepare a second-stage aqueous solution.
[0128] While stirring at a stirrer speed of 1000 rpm, the separable flask system was cooled to 25°C. The entire amount of the second-stage aqueous liquid was then added to the first-stage polymerization slurry. After the system was purged with nitrogen for 30 minutes, the flask was again immersed in a 70°C water bath to raise the temperature, and a polymerization reaction was carried out for 60 minutes to obtain a hydrogel polymer.
[0129] The flask was then immersed in an oil bath set at 125°C. Azeotropic distillation of n-heptane and water was performed, discharging 259.9 g of water from the system while refluxing the n-heptane. Then, 4.42 g (0.507 mmol) of a 2% by mass aqueous solution of ethylene glycol diglycidyl ether was added to the flask as a surface crosslinking agent, and the mixture was maintained at 83°C for 2 hours.
[0130] Then, n-heptane was evaporated and dried at 125°C, and further passed through a mesh of 850 The water-absorbing polymer particles had a physiological saline water retention capacity of 42 g / g, a water absorption rate of 39 seconds, and a median particle size of 360. m, and the water absorption of physiological saline under a load of 4.14 kPa is 20 ml / g.
[0131] [Evaluation of water-absorbent polymer particles] <Water retention capacity of normal saline solution> A cotton bag (cotton broadcloth No. 60, 100 mm wide x 200 mm long) containing 2.0 g of water-absorbent polymer particles was placed in a 500 ml beaker. 500 g of a 0.9% sodium chloride aqueous solution (physiological saline) was poured into the bag containing the water-absorbent polymer particles all at once, without forming a lump. The bag was then tied with a rubber band at the top and allowed to stand for 30 minutes to allow the water-absorbent polymer particles to swell. After 30 minutes, the bag was dehydrated for 1 minute using a dehydrator (Kokusan Co., Ltd., Product No. H-122) set to a centrifugal force of 167 G. The mass of the bag, including the swollen gel after dehydration, Wd (g), was measured. The same procedure was repeated without adding the water-absorbent polymer particles, and the empty mass of the wet bag, We (g), was measured. The saline water retention capacity was calculated using the following formula.
[0132] Water retention of saline solution (g / g) = [Wd-We] / 2.0 <Measurement of water absorption rate by eddy current method> In a constant temperature water bath, 50±0.1 g of normal saline solution adjusted to 25±0.2°C was weighed in a 100 mL beaker and stirred with a magnetic stirring bar (8 mm The solution was stirred at 600 rpm using a non-ringed container (a 30 mm x 30 mm ring) to generate a vortex. 2.0 ± 0.002 g of water-absorbent polymer particles were added to the physiological saline solution all at once. The time (in seconds) from the addition of the water-absorbent polymer particles to the point where the vortex at the liquid surface converged was measured. This time was used as the water absorption rate of the water-absorbent polymer particles. This water absorption rate is also expressed as the vortex method or vortex time.
[0133] <Median Particle Size (Particle Size Distribution) of Water-Absorbent Polymer Particles> 50 g of water-absorbent polymer particles were used for median particle size (particle size distribution) measurement. m sieve, mesh size 500 m sieve, mesh size 425 m sieve, mesh size 300 m sieve, mesh size 250 m sieve, mesh size 180 m sieve, mesh size 150 A JIS standard sieve was assembled using a sieve and a receiving tray of 100 m in this order. Water-absorbent polymer particles were placed on the top sieve of the assembly and shaken for 20 minutes using a Ro-Tap shaker for classification. After classification, the mass percentage of the water-absorbent polymer particles remaining on each sieve relative to the total mass was calculated to determine the particle size distribution. This particle size distribution was determined by cumulatively adding the particles on the sieves in order from the particle size with the largest particle size. The relationship between the sieve mesh size and the cumulative mass percentage of the water-absorbent polymer particles remaining on the sieves was plotted on logarithmic probability paper. By connecting the plots on the probability paper with a straight line, the particle size corresponding to 50% of the cumulative mass percentage was determined as the median particle size.
[0134] <Water absorption of physiological saline solution under a load of 4.14 kPa> Water absorption of saline solution under 4.14kPa load (water absorption under load) The measurement is performed using a measuring device schematically shown in the figure. The measurement is performed twice on a type of water-absorbent polymer particles, and the average value is obtained. The measuring device comprises a burette portion 1, a fixture 3, a catheter 5, a stand 11, a measuring table 13, and a measuring portion 4 placed on the measuring table 13. The burette portion 1 comprises: a burette 21 with a scale, a rubber stopper 23 that tightly covers the opening at the top of the burette 21, a stopcock 22 connected to the front end of the lower portion of the burette 21, an air inlet tube 25 connected to the lower portion of the burette 21, and a stopcock 24. The burette portion 1 is fixed by the fixture 3. The flat measuring table 13 has a through hole 13a with a diameter of 2 mm formed in its center, and is supported by the stand 11 with a variable height. The through hole 13a of the measuring table 13 and the stopcock 22 of the burette portion 1 are connected via the catheter 5. The inner diameter of the catheter 5 is 6 mm.
[0135] The measuring unit 4 comprises a cylinder 31 made of organic glass, a polyamide mesh 32 bonded to one opening of the cylinder 31, and a weight 33 movable in the vertical direction within the cylinder 31. The cylinder 31 is placed on the measuring table 13 via the polyamide mesh 32. The inner diameter of the cylinder 31 is 20 mm. The mesh size of the polyamide mesh 32 is 75 mm. The weight 33 has a diameter of 19 mm and a mass of 119.6 g, and as described later, can apply a load of 4.14 kPa (0.6 psi) to the water-absorbing polymer particles 10 a uniformly arranged on the polyamide net 32 .
[0136] First, close the stopcock 22 and stopcock 24 of the burette section 1, and inject 0.9% by mass saline solution adjusted to 25°C into the burette 21 from the upper opening of the burette 21. Next, after tightly capping the upper opening of the burette 21 with the rubber stopper 23, open the stopcock 22 and stopcock 24. Fill the interior of the catheter 5 with 0.9% by mass saline solution 50 so that no bubbles enter. Adjust the height of the measuring table 13 so that the height of the water surface of the 0.9% by mass saline solution reaching the through hole 13a is the same as the height of the upper surface of the measuring table 13. After adjustment, read the height of the water surface of the 0.9% by mass saline solution 50 in the burette 21 using the scale on the burette 21, and use this position as the zero point (the reading value at time 0 seconds).
[0137] In the measuring unit 4, 0.10 g of water-absorbent polymer particles 10a were evenly distributed on a polyamide mesh 32 within a cylinder 31. A weight 33 was placed on the water-absorbent polymer particles 10a. The cylinder 31 was positioned so that its center aligned with the catheter opening at the center of the measuring table 13. The amount of saline solution reduced in the burette 21 (i.e., the amount of saline solution absorbed by the water-absorbent polymer particles 10a) Wc (ml) was read 60 minutes after the water-absorbent polymer particles 10a began absorbing saline solution from the catheter 5. The saline absorption performance of the water-absorbent polymer particles 10a under a load of 4.14 kPa was calculated using the following formula.
[0138] Water absorption of saline solution under a load of 4.14 kPa (ml / g) = Wc (ml) / mass of water-absorbent polymer particles (g) [Preparation of activated carbon] Prepared BET specific surface area of 1345m 2 / g, median particle size is 46 m, activated carbon (Carboraffin-6, manufactured by Osaka Gas Chemical Co., Ltd.) with an ignition residue of 0.4%, a drying loss of 3.2%, a pH of 4.9, and a crushed shape.
[0139] [Evaluation of activated carbon] <Median particle size of activated carbon (laser diffraction)> The median particle size (D50 (median diameter), volume basis) of the activated carbon used was measured using a laser diffraction particle size distribution analyzer (SALD2300, manufactured by Shimadzu Corporation).
[0140] <BET specific surface area of activated carbon> 0.1 g of the activated carbon to be measured was dried at 60°C for 24 hours under degassing conditions using a pretreatment apparatus (Microtrac Bel, BELPREP VAC II). Then, an adsorption isotherm was measured at 77 K using a specific surface area measurement apparatus (Microtrac Bel, BELSORP MINI II) using nitrogen as the adsorption gas. The specific surface area was calculated from the multipoint BET curve and used as the BET specific surface area of the activated carbon.
[0141] [Production of Water-Absorbent Resin Composition] <Example 1> Silver-zinc zeolite (Zeomic HD10N, median particle size 2.1, manufactured by Zeomic Co., Ltd.) as a deodorant containing an antimicrobial metal was added to 100 parts by mass of the water-absorbing polymer particles obtained in the production example. m, BET specific surface area 653m 2 / g) and 0.10 parts by mass of the above-mentioned activated carbon as a porous deodorant were mixed using a cross-rotating mixer manufactured by Meiwa Industry Co., Ltd. at a rotation speed of 50 rpm and a revolution speed of 50 rpm for 30 minutes to obtain a water-absorbent resin composition.
[0142] The median particle size and BET specific surface area of the antimicrobial metal-containing deodorant were measured by the same measurement method as that of the activated carbon described above.
[0143] <Example 2> A water-absorbent resin composition was obtained by the same method as in Example 1 except that the added amount of the activated carbon was changed to 0.30 parts by mass.
[0144] <Example 3> A water-absorbent resin composition was obtained by the same method as in Example 1 except that the added amount of the silver-zinc zeolite was changed to 0.10 parts by mass.
[0145] <Example 4> A water-absorbent resin composition was obtained by the same method as in Example 1 except that the amount of the silver-zinc zeolite added was 0.10 parts by mass and the amount of the activated carbon added was 0.30 parts by mass.
[0146] <Example 5> A water-absorbent resin composition was obtained by the same method as in Example 1 except that the amount of the silver-zinc zeolite added was 0.06 parts by mass and the amount of the activated carbon added was 0.20 parts by mass.
[0147] Comparative Example 1 A water-absorbent resin composition was obtained by the same method as in Example 1 except that the amount of the silver-zinc zeolite added was 0.015 parts by mass and the amount of the activated carbon added was 0.05 parts by mass.
[0148] Comparative Example 2 A water-absorbent resin composition was obtained by the same method as in Example 1 except that the amount of the silver-zinc zeolite added was 0.06 parts by mass and the amount of the activated carbon added was 0.03 parts by mass.
[0149] Comparative Example 3 A water-absorbent resin composition was obtained by the same method as in Example 1 except that the amount of the silver-zinc zeolite added was changed to 0.015 parts by mass and no activated carbon was added.
[0150] Comparative Example 4 A water-absorbent resin composition was obtained by the same method as in Example 1 except that the amount of the silver-zinc zeolite added was changed to 0.03 parts by mass and no activated carbon was added.
[0151] <Comparative Example 5> A water-absorbent resin composition was obtained by the same method as in Example 1 except that the amount of the silver-zinc zeolite added was changed to 0.06 parts by mass and no activated carbon was added.
[0152] <Comparative Example 6> A water-absorbent resin composition was obtained by the same method as in Example 1 except that the amount of the silver-zinc zeolite added was changed to 0.10 parts by mass and no activated carbon was added.
[0153] <Comparative Example 7> A water-absorbent resin composition was obtained by the same method except that the silver-zinc zeolite of Example 1 was not added and the added amount of activated carbon was 0.03 parts by mass.
[0154] <Comparative Example 8> A water-absorbent resin composition was obtained by the same method except that the silver-zinc zeolite of Example 1 was not added and the added amount of activated carbon was 0.05 parts by mass.
[0155] <Comparative Example 9> A water-absorbent resin composition was obtained by the same method except that the silver-zinc zeolite of Example 1 was not added and the added amount of activated carbon was 0.10 parts by mass.
[0156] <Comparative Example 10> A water-absorbent resin composition was obtained by the same method except that the silver-zinc zeolite of Example 1 was not added and the added amount of activated carbon was 0.20 parts by mass.
[0157] <Comparative Example 11> A water-absorbent resin composition was obtained by the same method except that the silver-zinc zeolite of Example 1 was not added and the added amount of activated carbon was 0.30 parts by mass.
[0158] <Reference Example 1> As Reference Example 1, the water-absorbing polymer particles obtained in the Production Example were used.
[0159] [Evaluation of water-absorbent resin composition] <Ammonia production inhibition test> Artificial urine was prepared by dissolving 25.0 g of urea, 9.0 g of sodium chloride, 0.6 g of magnesium sulfate heptahydrate, 0.7 g of calcium lactate, 4.0 g of potassium sulfate, 2.5 g of ammonium sulfate, and 0.1 g of L-cystine in 958.1 g of distilled water. Separately, urease (1000 U / mL of a 50% glycerol solution derived from jack bean, manufactured by Merck) was diluted in distilled water to 2 U / mL to prepare a urease solution. 0.500 g of the water-absorbent resin composition or water-absorbent polymer particles was placed in a sterile petri dish (88 mm diameter, 17 mm height). A test solution (prepared by mixing 30.0 mL of the artificial urine and 1.0 mL of the urease solution) was added to swell the sample. After adding the test solution, the sample was sealed in a 2L polyester sampling bag (PAAAK2, manufactured by GLSciences Co., Ltd.). The air in the bag was purged, and 900 mL of dry air was then added. The samples were then stored at 35°C, and after 24 hours, ammonia concentrations were measured using a gas detector tube (GASTEC Corporation, Ammonia 3L, 3La, 3M). The measured values and the deodorization rate calculated using the following formula 1 are shown in Table 1.
[0160] Formula 1: Deodorization rate (%) = [(ammonia concentration of Reference Example 1 - ammonia concentration of Examples or Comparative Examples) / ammonia concentration of Reference Example 1] × 100 <Dust generation test> Prepare a 500mL glass suction flask. Set a SUS hopper (88mm top inner diameter x 18mm foot inner diameter) so that the height from the bottom of the flask to the hopper outlet is 180mm. Connect the suction port of the flask to a dust meter (digital indicator LD-5R, manufactured by Shibata Scientific Co., Ltd.) via a glass tube (7.7mm inner diameter x 300mm length). Place 3.0g ± 0.1g of the water-absorbent resin composition as a sample into the hopper. Pull out the hopper flap while pressing the start button on the dust meter. Record the count after one minute (count for sample (A)). Perform a blank test before measuring the sample. Calculate the count during the blank test (B). Calculate the dust generation rate using the following formula.
[0161] Dust generation rate (cpm) = A - B Where A represents the count of the sample (cpm), and B represents the count of the blank test (cpm).
[0162] The above-mentioned dust generation degree measurement was performed three times on one sample, and the average value was adopted as the dust generation degree of the sample. The results are shown in Table 2.
[0163] [Table 1] [Table 2] As shown in Table 1, the deodorization rate of Comparative Example 9, in which the porous deodorant content x in the water-absorbent resin composition was 0.10 mass%, was 20%, while the deodorization rate of Comparative Example 6, in which the antimicrobial metal-containing deodorant content y in the water-absorbent resin composition was 0.10 mass%, was 60%. In contrast, the deodorization rate of Example 3, in which the porous deodorant content x in the water-absorbent resin composition was 0.10 mass% and the antimicrobial metal-containing deodorant content y was 0.10 mass%, was extremely high, at 98%. The results of Comparative Examples 6 and 9 (the combined deodorization rates of Comparative Examples 6 and 9 were also 80%) demonstrate that the antimicrobial metal-containing deodorant and the porous deodorant exhibit an unexpected synergistic effect. The synergistic effect of the deodorization rate of the water-absorbent resin composition shown in Table 2 is obtained by dividing the deodorization rate of the examples by the sum of the deodorization rates of the comparative examples using each deodorant alone. For example, the synergistic effect of Example 3 is calculated as the deodorization rate of Example 3 (98) / (the deodorization rate of Comparative Example 9 (20) + the deodorization rate of Comparative Example 6 (60)). If the value exceeds the reference value of 1.00, it can be said that the synergistic effect is exerted.
[0164] Furthermore, as can be seen from the results shown in Table 2, among the water-absorbent resin compositions of Examples 1 to 5, Examples 1, 2, and 5 were excellent in dust generation, and Example 1 was particularly excellent.
[0165] Description of Reference Numerals 1. Burette 3. Fixture 4 Measurement unit 5 Catheter 10a Water-absorbing polymer particles 11 racks 13. Measuring platform 13a Through hole 21 burette 22 cock 23 rubber stopper 24 cock 25 Air inlet pipe 31 Cylinder 32 Polyamide mesh 33 Counterweight 50 Salt water.
Claims
1. A water-absorbent resin composition, characterized in that Contains a deodorant containing an antimicrobial metal, a porous deodorant, and water-absorbing polymer particles, The ratio X / Y of the content X (parts by mass) of the porous deodorant to the content Y (parts by mass) of the antimicrobial metal-containing deodorant is 0.8 or more. The sum of the content x (mass %) of the porous deodorant and the content y (mass %) of the antimicrobial metal-containing deodorant in the entire water-absorbing resin composition, that is, x+y, is 0.10 mass % or more.
2. The water-absorbent resin composition according to claim 1, wherein The sum of the content x (mass %) and the content y (mass %), that is, x+y, is 0.50 mass % or less.
3. The water-absorbent resin composition according to claim 1 or 2, wherein The antimicrobial metal contained in the antimicrobial metal-containing deodorant includes at least one selected from the group consisting of silver, copper, zinc, bismuth, cobalt, aluminum, and nickel.
4. The water-absorbent resin composition according to claim 1 or 2, wherein The antimicrobial metal-containing deodorant includes at least one selected from the group consisting of silver powder, silver (I) chloride, silver (I) oxide, and a substance carrying at least one metal ion of silver ion and zinc ion.
5. The water-absorbent resin composition according to claim 1 or 2, wherein The porous deodorant includes at least one selected from the group consisting of activated carbon, silicon dioxide, and silicate.
6. The water-absorbent resin composition according to claim 1 or 2, wherein The median particle size of the deodorant containing antibacterial metal is 0.1 μ m~100 μ m, the median particle size of the porous deodorant is 1 μ m~100 μ m.
7. An absorbent article, characterized in that: Contains a deodorant containing an antimicrobial metal, a porous deodorant, and water-absorbing polymer particles, The ratio X / Y of the content X (parts by mass) of the porous deodorant to the content Y (parts by mass) of the antimicrobial metal-containing deodorant is 0.8 or more. The sum of the content rate x (mass %) of the porous deodorant and the content rate y (mass %) of the antimicrobial metal-containing deodorant, i.e., x+y, based on the total amount of the antimicrobial metal-containing deodorant, the porous deodorant, and the water-absorbing polymer particles, is 0.10 mass % or more.
Citation Information
Patent Citations
Moisture-controlling material for decorative material and dressed material by its use
JP2001323155A